2013 13th International Conference on Quality Software 2013
DOI: 10.1109/qsic.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Adoption of Software Testing in Open Source Projects

Abstract: Abstract-In software engineering, testing is a crucial activity that is designed to ensure the quality of program code. For this activity, software teams spend substantial resources constructing test cases to thoroughly assess the correctness of software functionality. What is the proportion of open source projects that include test cases? What is the effect of number of developers on the number of test cases?In this study, we explore open source projects and investigate the correlation between the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…When investigating the presence or absence of tests, Kochar et al mined 20,000 open-source projects and found that 62% contain unit tests [36]. LaToza et al [37] surveyed 344 software engineers, testers and architects at Microsoft, with 79% of the respondents indicating to use unit tests.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…When investigating the presence or absence of tests, Kochar et al mined 20,000 open-source projects and found that 62% contain unit tests [36]. LaToza et al [37] surveyed 344 software engineers, testers and architects at Microsoft, with 79% of the respondents indicating to use unit tests.…”
Section: Related Workmentioning
confidence: 99%
“…The work presented in this paper differs from the aforementioned works in that the data that we use is not obtained (1) from a software repository [3,4,27,36,41] or (2) purely by means of a survey or interview [37][38][39]42]. Instead, our data is automatically gathered inside the IDE, which makes it (1) more fine-grained than commitlevel activities and (2) more objective than surveys.…”
Section: Related Workmentioning
confidence: 99%
“…Thus the effectiveness of a dynamic approach is often dependent on the quality of a test suite. Unfortunately, Kocchar et al have shown that the adoption of software testing in many projects is often poor [16]. Spectrum-based fault localization, e.g., [2,14,18,29] and model-based fault localization, e.g., [10,22], are some of the well known dynamic approaches.…”
Section: Bug Localizationmentioning
confidence: 99%
“…They find that only 14% of the active projects use pull-requests and 60% of the pull-requests are processed in a day. Kochhar et al investigate 50,000 projects to study the correlation between the presence of test cases and various project development characteristics, including the lines of code and the size of development teams [26], [27].…”
Section: Other Large Scale Studies On Githubmentioning
confidence: 99%